Cell Membrane–Camouflaged Colloid Motors for Biomedical Applications. Issue 5 (8th July 2018) - Gao, Changyong; Lin, Zhihua; Lin, Xiankun; He, Qiang
Abstract: Natural cell membrane–camouflaged colloid motors can not only convert the surrounding environmental energy into directed movement but also possess the functions of natural cell membranes. They can autonomously move and are guided by exogenous (e.g., chemical fuel, light, magnetic field, and ultrasound) and endogenous (i.e., chemotaxis) stimuli. These biointerfacing colloid motors with efficient drug loading/transporting capacity, prolonged blood circulation, and antibiofouling and specific targeting abilities are expected to open up opportunities for various biomedical applications and are recognized as the next‐generation therapeutic systems. In this progress report, the authors highlight the recent progress in research on cell membrane–coated colloid motors, as well as their potential for biomedical applications. The limitations and challenges of these colloid motors for in vivo applications are also addressed. Abstract : Cell membrane–camouflaged colloid motors based on colloid motors and natural cell membranes present the next‐generation therapeutic system. Recent progress in synthetic colloid motors, cell membrane coating technology, and cell membrane–camouflaged motors is summarized.